Caspase dependence of the death of neonatal retinal ganglion cells induced by axon damage and induction of autophagy as a survival mechanism - Sternberg,C. (2010)
We examined the degeneration of post-mitotic ganglion cells in ex-vivo neonatal retinal explants following axon damage. Ultrastructural features of both apoptosis and autophagy were detected. Degenerating cells reacted with antibodies specific for activated caspase-3 or -9, consistent with the presence of caspase activity. Furthermore, peptidic inhibitors of caspase-9, -6 or -3 prevented cell death (100 µM Ac-LEDH-CHO, 50 µM Ac-VEID-CHO and 10 µM Z-DEVD-fmk, respectively). Interestingly, inhibition of autophagy by 7-10 mM 3-methyl-adenine increased the rate of cell death. Immunohistochemistry data, caspase activation and caspase inhibition data suggest that axotomy of neonatal retinal ganglion cells triggers the intrinsic apoptotic pathway, which, in turn, is counteracted by a pro-survival autophagic response, demonstrated by electron microscopy profiles and pharmacological autophagy inhibitor.